Analisis Tingkat Kepuasan Peternak Plasma pada Kemitraan PT. Binuang Rizky Gemilang - Ramdan, Muhammad; Indah Laela Rahmah, Ulfa; Adam Yuliandri, Lili (Tropical Livestock Science Journal, 2025)
This study aims to analyze the level of satisfaction and analyze the factors that influence the level of satisfaction of plasma breeders towards the core company.The research was conducted in July 2025. The research method used is a survey with descriptive analysis method, using CAST calculation to analyze the level of satisfaction and multiple linear regression analysis to analyze the factors that influence the level of satisfaction. Determination of respondents was carried out using purposive sampling method as many as 32 respondents. The variables observed were satisfaction level, age of the farmer, education level, length of farming, length of partnership, and population size. The results showed that the level of satisfaction of plasma farmers with the core company was 81.31%, which means that the level of satisfaction is quite good. Based on the results of multiple linear regression analysis, it shows that there are no influential variables.